Forecasting cyber crimes in the age of the metaverse - Elshenraki, Hossam Nabil (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series, 2024)
"This book forecasts by scientific method the expected crimes in the meta verse and how it will affect the police capabilities in combating crimes"--